DIAGNOSIS OF AIRPLANE’S WING SURFACE USING THE BAYESIAN NETWORKS - Казак, В.; Булка, Л.; Вакарова, А.; Гладинюк, Б. (Science-based technologies, 2010)
A used technique for determining the likelihood of damage to the external shape of the aircraft using the Bayesian networks. They can not only use prior experience of experts in the relevant subject area, but also take into account the objective information obtained during the experiments or accrued as a result of long observation.